The Product Life Cycle as the Mediating Role of Reverse Logistics on Supply Chain Performance in the Food Industries of East Java - Niza Nurmalasari; Mov Rivqi Amin; Farida Tri Hastuti; Ina Syarifah; Hendrick Hernando (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2023)
The management of product returns, commonly known as reverse logistics (RL), has emerged as a critical concern for organizations in recent times. This is primarily due to the rising volume of returned goods, which has prompted companies to take notice and address the issue, especially in the food industry. The objective of this study is to examine the Impact of Reverse Logistics on the Supply Chain Performance mediated by Product Life Cycles in the food industry in East Java, Indonesia. The methodology employed in this study is explanatory methods and illustrates the interrelationships between variables through hypothesis testing using SPSS 22 and PLS. Furthermore, a method of surveying was implemented to retrieve data from purposeful sampling for 30 respondents from different companies who are proficient and possess reverse logistics. The results indicate that utilizing of supply chain performance indicators or Key Performance Indicators (KPIs) can assist organizations in gauging the effectiveness of their supply chain performance in accomplishing reverse logistics aims concerning expense management and heightened profitability through the contemplation of the product life cycle.